Evaluation of a unilateral neck mass in a 16-year-old female: Kikuchi-Fujimoto disease with superimposed bacterial lymphadenitis. (October 2020) - Burns, Joseph; Pathania, Shivany; Griesser, Rebecca; Norelli, Jolanta; Gilgeours, Kelly; Tugetman, Jessica; Palumbo, Nancy
The evaluation of pediatric neck masses offers the opportunity for consideration of a diverse range of pathologies, from infectious to neoplastic. A 16-year-old female presented with 2 weeks of worsening swelling and pain of a left-sided neck mass. Findings were consistent with Epstein–Barr virus and cytomegalovirus coinfection, but considering profound lymphadenopathy of the supraclavicular, mammillary, and axillary chains, further investigations were undertaken. Hematopathologic examination demonstrated necrotizing lymphadenitis, consistent with Kikuchi-Fujimoto disease. A diagnosis of Kikuchi-Fujimoto disease alongside chronic bacterial lymphadenitis was made on the basis of her response to clindamycin, and the chronic course of her illness and subsequent persistence of the swelling managed on an outpatient basis. The case study describes the initial diagnostic considerations and management as well as a review of the disease pathology.